Concentrated photovoltaic thermal systems using Fresnel lenses – A review. (2021) - Verma, Shashikant; Verma, Abhishek; Kumar, Vivek; Gangil, Brijesh
Abstract: The emergence of solar PV systems is an important area of research due to the availability of these photovoltaics at cheaper rates. The emerging technology of PV is already being used in many parts of the world as a source of energy to reduce dependence on non-renewable sources. The recent popularity of Photovolatalic Thermal systems also known as PV/T systems is in consideration due to their increased efficiency over conventional PV systems. The authors in this paper intend to show the various aspects of PV integrated with thermal systems, the PV/T systems. The Fresnel lens is used as a concentrator for focussing the sunlight on the PV cells. Various publications about Fresnel lenses show that they are of prime importance in the cogeneration of power and heat effectively. Various thermal and electrical aspects, modifications in the conventional PV/T systems have been discussed. To conclude this review paper, problem areas associated with the PV/T systems have been mentioned. Further research is suggested to improve the design, effectiveness, and reduce the overall cost of the system.